Software selection and deployment for library cooperation and resource sharing among academic libraries in South-West Nigeria (2015)
This study assessed software selection and seployment sractices for library cooperation and resource sharing among aacademic libraries in South-West Nigeria. The purposive sampling technique was adopted and data collection instruments were questionnaire and interview. All of the 39 universities in the South- West zone were chosen and copies of questionnaire were administered to a representative of each academic library. 37 questionnaires were received. The descriptive statistical method of analysis was used. It was discovered that there is no form of cooperation and resource sharing among the academic libraries presently. The study recommends that National Universities Commission (NUC) should make automation a requirement for all academic libraries in Nigeria and recommend particular software(s) for cooperation and resource sharing to be possible among academic libraries among others.